Enhancing the annual yield via nitrogen fertilizer application optimization in the direct seeding ratoon rice system - Li, Yang; Zhang, Zuolin; Wang, Benfu; Zhang, Zhisheng; Lin, Yiyue; Cheng, Jianping (Frontiers in Plant Science, 2024)
Direct seeding ratoon rice (DSRR) system is a planting method that can significantly increase grain yield, improving light and temperature utilization efficiency and reducing labor input. However, the current nitrogen fertilizer management method which does not aim at the seedling emergence and development characteristics of DSRR just is only based on the traditional method of transplanting ratoon rice, and which is not conducive to the population development and yield improvement. To determine the suitable nitrogen fertilizer application optimization, we set four nitrogen fertilizer application treatments (N0, no nitrogen fertilizer; N1, traditional nitrogen fertilizer; N2, transferring 20% of total nitrogen from basal fertilizer to tillering stage; N3, reducing total nitrogen by 10% from N2 tillering fertilizer) on a hybrid rice "Fengliangyouxiang1 (FLYX1)" and an inbred rice "Huanghuazhan (HHZ)" under DSRR. The effects of treatments on dry matter accumulation, root growth and vigor, leaf area index, leaf senescence rate and yield were investigated. Our results demonstrated that the yield of main crop in N2 treatment was the highest, which was 63.3%, 6.6% and 8.8% higher than that of N0, N1 and N3 treatment, respectively, mainly due to the difference of effective panicle and spikelets number per m 2 . The average of two years and varieties, the annual yield of N2 was significant higher than that of N1 and N3 by 4.94% and 8.55%, respectively. However, there was no significant difference between the annual yields of N1 and N3. N2 treatment had significant effects on the accumulation of aboveground dry matter mass which was no significant difference in 20 days after sowing(DAS), but significant difference in 50 DAS. Meanwhile, the root activity and the leaf senescence rate of N2 treatment was significant lower than that of other treatments. In summary, "20% of total nitrogen was transferred from basal fertilizer to tillering stage" can improve the annual yield and main crop development of DSRR system. Further reducing the use of nitrogen fertilizer may significantly improve the production efficiency of nitrogen fertilizer and improve the planting income in DSRR system.